A Study on the adoption and use of cellphones of journalists - Ramayrat, Maria Erica Ciara Ardan; Rara, Maria Cristina I. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2011)
"This study explains the cultural factors that influenced the intention of print, radio, TV and online journalists to use mobile phones, based on the initial findings of researchers Van Biljon and Kotze's (2008). In addition, it also looks into the ways journalists make use of the mobile phone into their practices. A survey questionnaire has been formulated by the researcher and interviews have been conducted in order to gather data, that would address the objectives of the study. A total of 125 journalists participated in the study- 100 participated in the survey while the remaining 25 participated in an interview. The results show that among the cultural factors described by Biljon and Kotze' (2008), perceived usefulness, personal and facilitating conditions are the most significant variables that largely determined the journalists' intention to adopt a mobile phone. It also showed that the mobile phone has several uses for journalists, depending on their category of work whether they are from print, radio, TV or online. In general, the mobile phone has been found to be actively used for data gathering more than it is used for producing and transmitting news and other information."
Thesis (A.B. Journalism)--University of the Philippines Diliman